2018
DOI: 10.1111/cas.13820
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of resistance mechanisms for epidermal growth factor receptor‐tyrosine kinase inhibitors based on plasma analysis by digital polymerase chain reaction and next‐generation sequencing

Abstract: Liquid biopsy offers a potential alternative to tissue biopsy for detection of genetic alterations in cancer, and it has been introduced into clinical practice to detect the tyrosine kinase inhibitor (TKI) resistance‐conferring T790M mutation of epidermal growth factor receptor (EGFR) in patients with non‐small‐cell lung cancer (NSCLC). We prospectively collected tumor and plasma samples from 25 NSCLC patients who harbored activating mutations of EGFR and experienced failure of treatment with afatinib. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
(105 reference statements)
1
26
0
Order By: Relevance
“…NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy. [24][25][26][27][28][29][30][31] Our findings suggest that the monitoring of allele frequency for EGFRactivating mutations in cfDNA by NGS may also be useful for the prediction of EGFR-TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy. [24][25][26][27][28][29][30][31] Our findings suggest that the monitoring of allele frequency for EGFRactivating mutations in cfDNA by NGS may also be useful for the prediction of EGFR-TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 76%
“…Such a pattern was also evident for the allele frequency of EGFR ‐activating mutations (the ratio of the number of activating mutations to the total number of EGFR alleles) as determined by ddPCR (data not shown). NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy . Our findings suggest that the monitoring of allele frequency for EGFR ‐activating mutations in cfDNA by NGS may also be useful for the prediction of EGFR‐TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Multiple studies have confirmed that it was reliable to identify guideline-recommended biomarkers in patients with mNSCLC through a comprehensive cfDNA test, especially with the highly sensitive and specific NGS-based detection. [67,68] For example, in the Non-invasive versus Invasive Lung Evaluation (NILE) study, plasma NGS tests in previously untreated mNSCLC showed high sensitivity and specificity with high tissue concordance, significantly faster return of results, and was even more rapidly and completely than the standard-of-care tissue genotyping [67]. The convenience, minimal invasiveness and repeatability of liquid biopsy enable the utility of cfDNA detection as a significant way not only for the detection of targetable driver alterations, but also for exploration of mechanisms of resistance to such drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that TP53 concurrent mutation might adversely impact the survival of patients with advanced NSCLC treated with EGFR-TKIs or ALK-TKIs for oncogenic EGFR or ALK mutations [27][28][29][30]. In addition, some preclinical studies indicated that TP53 might be one of the mechanisms that potentially confer resistance to EGFR-and ALK-TKIs treatment [31,32]. However, several other studies found no correlation between TP53 mutations and survival of patients with EGFR-mutated advanced NSCLC and treated with EGFR-TKIs [33][34][35].…”
Section: Nsclcmentioning
confidence: 99%